Efficacy of thermal treatments against rice weevil, Sitophilus oryzae - SINGH, S P; BHALLA, SHASHI; GUPTA, KAVITA; MEENA, D S; DUBEY, S C (The Indian Journal of Agricultural Sciences, 2019)
Thermal treatments at 35, 40, 45, 50, 55 and 60±1°C for a period of 1, 2 and 3 h were evaluated against Sitophilus oryzae adult along with germination test and vigour index of wheat seeds. No mortality of insect was observed at 35± 1°C after 1, 2 and 3 h of exposure while 63.33, 73.33 and 83.33% mortality of adult insect was recorded at 40±1°C after 1, 2 and 3 h of exposure respectively. However, 100% mortality of S. oryzae adult was observed at 45, 50, 55 and 60±1°C for all time periods. Almost 100% germination of wheat seed was observed under all the temperature treatments and durations as above. No significant difference in vigour index of wheat seed was recorded at different temperatures for all the three duration of exposure.